Causal relationship between tea intake and cardiovascular diseases: A Mendelian randomization study - Gao, Ning; Ni, Ming; Song, Jiangwei; Kong, Minjian; Wei, Dongdong; Dong, Aiqiang (Frontiers in Nutrition, 2022)
Background Although studies suggest that tea consumption is associated with a reduced risk of cardiovascular disease (CVD). There is no unified conclusion about the potential relationship between tea drinking and CVD. We used a two-sample Mendelian randomized (MR) analysis to systematically explore the causal relationship between tea intake and CVD subtypes for the first time. Furthermore the mediating effect of hypertension was also explored by a two-step MR. Methods Genetic instruments for tea intake were identified from a genome-wide association studies (GWAS) involving 447,485 people. Summary data on cardio-vascular disease came from different GWAS meta-analysis studies. In the first step we explored the causal effect of tea intake and CVD. In the second step, we examined the association of hypertension with heart failure and ischemic stroke and estimated the mediating effect of hypertension. Inverse variance weighted MR analysis was used as the primary method for causal analysis. A further sensitivity analysis was performed to ensure robustness of the results. Results One standard deviation increase in tea intake was associated with a 25% (OR = 0.75, 95%CI = 0.61–0.91, p = 0.003) lower risk of hypertension, a 28% (OR = 0.72, 95%CI = 0.58–0.89, p = 0.002) lower risk of heart failure, and a 29% (OR = 0.71, 95%CI = 0.55–0.92, p = 0.008) lower risk of ischemic stroke, respectively. And the association between tea drinking and the risk of heart failure and ischemic stroke may be mediated by hypertension. Sensitivity analyses found little evidence of pleiotropy. Conclusion Our two-sample MR analysis provided genetic evidence that tea intake was significantly associated with a reduced risk of hypertension, heart failure, and ischemic stroke, and that hypertension may be a potential mediator. Further large randomized controlled trials should be conducted to confirm the causal effect of tea consumption on cardiovascular disease risk.